Diagnóstico geoambiental no município de Batatais-SP - Caldas, Anildo Monteiro [UNESP] (2015)
The growing expansion of agricultural activities, without considering the potentialities and limitations of the land use constitutes a potential source of environmental degradation. This study was conducted in the Batatais County - SP, aiming to diagnose the areas of land use conflict. The methodological procedures used geographic information systems and remote sensing techniques to determine the roughness number (RN), by analyzing the physical characteristics of hydrological compartments. The distribution of the land use classes was confronted with the potential land uses and enabled the identification and quantification of the land uses conflicts. The map of the land uses conflict indicates that the municipal area of 452.46 km2 is in conflict zones, of which 28.67% are assigned to conflict - Class 1, that is, areas that shows risk and severe limitations for permanent crops and pasture